Nose Profile in the Population of Poland - Gralla, Gertruda (Anthropological Review, 1981)
On the material comprising 64.745 individuals aged 0-65 years representing both sexes collected by the Anthropometric Committee of the Polish Academy of Sciences the author has determined frequencies ‘of nose profile categories by age.